Legislation Policy to the Elimination of Minimal Capital Legal Entities for Limited Liability Companies - Roma, Muhammad Hatta; Miqat, Nurul; Purnamasari, Andi Intan; Syamsuddin, Adiesty Septhiany Prihatiningsih; Patila, Manga (Amsir Law Journal, 2021)
The purpose of this study is to analyze the factors that hinder the implementation of government policies against the elimination of minimal capital of legal entities as an effort to develop MSME to improve the regional economy in Palu of Central Sulawesi. This research was an empirical research method using a qualitative descriptive approach. The results showed the factors inhibiting the implementation of government policy on the elimination of minimal capital of legal entity making is the lack of information about Government Regulation Number 29 of 2016 concerning Changes in The Basic Capital of The Establishment of Limited Liability Companies, Constraints on the requirements of making Limited Liability Companies both due to large capital constraints for the manufacture of Limited Liability Companies and Due to Administrative System Constraints that are quite difficult, and the latter is the Orientation of Individualist Thinking.